2017
DOI: 10.1093/annonc/mdx484
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival using specialized multidisciplinary board in sarcoma patients

Abstract: The compliance to clinical practice guidelines and relapse-free survival of sarcoma patients are significantly better when the initial treatment is guided by a pre-therapeutic specialized MDTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
178
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(195 citation statements)
references
References 25 publications
8
178
0
9
Order By: Relevance
“…Adjuvant RT and PP were also associated with a better outcome. This finding is consistent with the nationwide French NetSarc reference work that observed a twofold increased R2 surgery outside the NetSarc center and threefold more secondary resection after primary surgery performed without multidisciplinary tumor board in other sarcoma types 18. In the present study, local surgery had a favorable impact on survival even for patients with metastatic RMS which is consistent with the MSKCC and French pediatric experience.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Adjuvant RT and PP were also associated with a better outcome. This finding is consistent with the nationwide French NetSarc reference work that observed a twofold increased R2 surgery outside the NetSarc center and threefold more secondary resection after primary surgery performed without multidisciplinary tumor board in other sarcoma types 18. In the present study, local surgery had a favorable impact on survival even for patients with metastatic RMS which is consistent with the MSKCC and French pediatric experience.…”
Section: Discussionsupporting
confidence: 92%
“…But in our study, patients older than 25 years received significantly less chemotherapy and numerous treatments. Surgical results were consistent with those previously reported 11, 12, 13, 15, 16, 17, 18, 19. The absence of surgery and incomplete resection were deleterious for OS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation has also been reported by Blay et al 7 suggesting significantly more R0 and less R2 resections, less reoperations, and higher relapse-free survival (RFS) and local RFS in reference centers.…”
Section: What Are the Remarkable Findings?supporting
confidence: 84%
“…2 In fact, recent data have demonstrated that sarcoma patients undergoing evaluation in a specialized multidisciplinary tumor board had better local relapse-free and relapse-free survival compared with patients who did not. 3 There is a growing body of evidence regarding the better outcome, specifically among RPS patients initially treated in specialized centers. [4][5][6][7] This disease, or in reality, family of diseases, is complex.…”
mentioning
confidence: 99%